Marx : a guide for the perplexed - Seed, John, 1950- (Guides for the perplexed., 2010)
"It is widely acknowledged that Karl Marx was one of the most original and influential thinkers of modern times. His writings have inspired some of the most important political movements of the past century and still has the power to arouse controversy today. Marx: A Guide for the Perplexed is a clear and thorough account of Marx's thought, his major works and theories, providing an ideal guide to the important and complex ideas of this major figure in the history of political thought. The book introduces key Marxist concepts and themes and examines the ways in which they have influenced philosophical and political thought. Geared towards the specific requirements of students who need to reach a sound understanding of Marx's ideas, the book provides a cogent and reliable survey of some of the most important debates surrounding his often controversial theories. This is the ideal companion to the study of this most influential and challenging of thinkers"--Provided by publisher.